O028/#376 Clinical benefit of mirvetuximab soravtansine in ovarian cancer patients with high folate receptor alpha expression: results from the soraya study. (4th December 2022) - Coleman, Robert L; Matulonis, Ursula; Lorusso, Domenica; Oaknin, Ana; Pignata, Sandro; Denys, Hannelore; Colombo, Nicoletta; Gorp, Toon Van; Konner, Jason; Marin, Margarita Romeo; Harter, Philipp; Murphy, Conleth; et al.
Abstract : Objectives: Mirvetuximab soravtansine (MIRV) is a first-in-class ADC comprising a folate receptor α (FRα)-binding antibody, cleavable linker, and maytansinoid DM4 payload. Here, we present updated data from the single-arm study SORAYA on the clinical benefit and safety of MIRV in FRα-high platinum-resistant ovarian cancer (PROC). Methods: Patients (N=106) received MIRV 6 mg/kg, adjusted ideal body weight, intravenously on Day 1 of a 3-week cycle. Patients must have received 1–3 prior therapies, including bevacizumab. FRα-high expression by immunohistochemistry (PS2+ ≥75%) was required. Responses were assessed by investigator using RECIST v1.1. Here we report tumor reduction and disease control rate (percent of patients with complete response, partial response, and stable disease of 12+ weeks). Results: Characteristics of 106 patients enrolled are in table 1 . Seventy-five patients (71%) experienced tumor reduction as their best response ( figure 1 ) and the disease control rate (DCR) was 51.4% (95% CI 41.5, 61.3). The confirmed ORR was 32.4% (95% CI 23.6, 42.2), the median duration of response was 6.9 months (95% CI 5.6, 8.1), and the median progression-free survival was 4.3 months (95% CI 3.7, 5.1). Most frequent treatment-related adverse events (TRAE; all, grade 3+) related to study drug included blurred vision (41%, 6%), keratopathy (36%, 9%), nausea (29%, 0%), and dry eye (23%, 2%). Seven percent of patients discontinued treatment due to a TRAE. Conclusions: MIRV demonstrated anti-tumor activity by tumor reduction and DCR in heavily pretreated patients with FRα-high PROC. These data support MIRV as a potential practice-changing, biomarker-driven therapy.